Graphite immobilisation in glass composite materials - Mayzan, Mohd Zul Hilmi (2015)
Irradiated graphite is a problematic nuclear waste stream and currently raises significant concern worldwide in identifying its long-term disposal route. This thesis describes the use of glass materials for the immobilisation of irradiated graphite prepared by microwave, conventional and sparks plasma sintering methods. Several potential glass compositions namely iron phosphate, aluminoborosilicate, calcium aluminosilicate, alkali borosilicate and obsidian were considered for the immobilisation of various loadings of graphite simulating irradiated graphite. The properties of the samples produced using different processing methods are compared selectively. An investigation of microwave processing using an iron phosphate glass composition revealed that full reaction of the raw materials and formation of a glass melt occurs with consequent removal of porosity at 8 minutes microwave processing. When graphite is present, iron phosphate crystalline phases are formed with much higher levels of residual porosity of up to 43 % than in the samples prepared using conventional sintering under argon. It is found that graphite reacts with the microwave field when in powder form but this reaction is minimised when the graphite is incorporated into a pellet, and that the graphite also impedes sintering of the glass. Mössbauer spectroscopy indicates that reduction of iron occurs with concomitant graphite oxidation. The production of graphite-glass samples using various powdered glass compositions by conventional sintering method still resulted in high porosity with an average of 6-17 % for graphite loadings of 20-25 wt%. Due to the use of pre-made glasses and controlled sintering parameters, the loss of graphite from the total mass is reduced compared to the microwaved samples; the average mass loss is < 0.8 %. The complication of iron oxidation and reduction is present in all the iron containing base glasses considered and this increases the total porosity of the graphite-glass samples. It is concluded that the presence of iron in the raw materials or base glasses as an encapsulation media for the immobilisation of the irradiated graphite waste is not advisable. The production of glass and graphite-glass samples based calcium aluminosilicate composition by spark plasma sintering method is found highly suitable for the immobilisation of irradiated graphite wastes. The advantages of the method includes short processing time i.e. < 40 minutes, improved sintering transport mechanisms, limited graphite oxidation, low porosity (1-4